Language and Gender in Riyam wa Kafa and Papa Sartre: A Lakoffian Reading - Hani Obaid Bany Saad, Raed; Saadi, Mohammed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This study analyzes gendered differences in novelistic language, drawing on Robin Lakoff’s theory of women’s language. It applies a descriptive–analytical and statistical method to two contemporary Arabic novels: Riyam wa Kafa by Hadiya Hussein and Papa Sartre by Ali Badr. The investigation addresses both the lexical and the syntactic–functional levels of the narrative corpus, focusing on phenomena such as color terms, oaths, derogatory expressions, intensifiers, hedges, repetition, exclamatives, colloquial expressions, imperative clauses, and questions. The findings indicate that the feminine discourse in Riyam wa Kafa is characterized by a dense affective lexicon, frequent repetition, a predominance of questions, and a marked presence of both hedges and intensifiers; color terms operate as expressive instruments for selfhood and female identity, reinforcing the narrative’s emotional and subjective dimensions. By contrast, Papa Sartre exhibits a more ironic and sarcastic register, with notable use of derogatory terms, direct imperatives, mocking repetition, and male-coded colloquial expressions. The comparative analysis further shows that several features diverge from Lakoff’s predictions: ostensibly masculine markers sometimes appear in women’s speech and vice versa, shaped by the socio-cultural context of the texts and the positioning of their characters. DOI: https://doi.org/10.54633/2333-024-056-027